ANALISIS NILAI PSIKOLOGIS DALAM NOVEL “BUYA HAMKA” KARYA AHMAD FUADI DAN IMPLEMENTASI DALAM PEMBELAJRAN SASTRA DI SMA CERDAS MURNI DELI SERDANG - Marie Muhammad; Rahmat Karolo (LPPM Universitas PGRI Silampari Lubuklinggau, 2025)
Literature is a medium that can be used for personal development. The psychological relevance of literature is crucial in today's world. As civilization progresses, humans often lose psychological control. This study aims to: (1) analyze and explain the characterization of the main character in Ahmad Fuadi's novel Buya Hamka; (2) examine the psychological aspects of the id in Ahmad Fuadi's novel Buya Hamka; (3) examine the psychological aspects of the ego in Ahmad Fuadi's novel Buya Hamka; (4) examine the psychological aspects of the superego in Ahmad Fuadi's novel Buya Hamka; and (5) analyze psychological values in Buya Hamka and implement literature learning at SMA Cerdas Murni Deli Serdang. This research is a qualitative descriptive study using a literary psychology approach using Sigmund Freud's theory. The data in this study consist of paragraphs from Ahmad Fuadi's novel Buya Hamka, as well as data sources from Ahmad Fuadi's novel Buya Hamka, and reference books related to the research. The sampling technique used was purposive sampling, data collection techniques with 3 techniques, namely reading techniques, note- taking techniques, and interview techniques. Research results (1) The characterization of the main character has its own characteristics (2) The aspects of Id, Ego, and Superego in the novel Buya Hamka by Ahmad Fuadi are very clear from several story fragments in this novel (3) In the context of the implementation of Indonesian language and literature learning at SMA Cerdas Murni Deli Serdang, the novel Buya Hamka by Ahmad Fuadi can be used as teaching material for novel material by discussing the content, structure, and language in the novel.